Biocompatible poly(N-(ω-acryloyloxy-n-alkyl)-2-pyrrolidone)s with widely-tunable lower critical solution temperatures (LCSTs): a promising alternative to poly(N-isopropylacrylamide). Issue 17 (13th April 2022) - Nishimura, Shin-nosuke; Nishida, Kei; Ueda, Tomoya; Shiomoto, Shohei; Tanaka, Masaru
Abstract : The biocompatible (co)polymers undergoes a thermal stimulus-driven liquid–liquid phase separation and form coacervates above the lower critical solution temperature (LCST). The LCSTs are able to be precisely controlled between 0 °C and 100 °C. Abstract : Poly( N -isopropylacrylamide) (PNIPAM) is one of the most commonly used thermo-responsive polymers. PNIPAM has a lower critical solution temperature (LCST) of approximately 32 °C, which is close to the temperature of the human body. Thus, it has long been used in biological applications. Although PNIPAM is commonly thought to be biocompatible and safe, it often induces blood clots, because the polymer contains a hydrogen-bond donor. Therefore, thermo-responsive materials with aprotic polar functional groups are needed as an alternative to PNIPAM. In this study, we focused on the pyrrolidone ring, which is an aprotic polar functional group that acts as a proton acceptor and has a high hydration ability, and prepared acrylate polymers containing this ring at the end of a side chain. These polymers, (poly( N -(ω-acryloyloxy- n -alkyl)-2-pyrrolidone)s (PNARPs) (R = methyl (Me), ethyl (Et), propyl (Pr), butyl (Bu), pentyl (Pn), and hexyl (Hx)), were readily synthesized by conventional free-radical polymerization. When the temperature was above the LCST, some of the PNARPs underwent liquid–liquid phase separation (LLPS) and formed coacervates in water. Simple copolymerization of the monomers, particularly the combination of NAEtP and NAHxP, resulted in copolymers with LCSTs that were able to be widely and precisely controlled between 0 °C and 100 °C in water and phosphate-buffered saline (−) ((PBS (−)). These(co)polymers also exhibited good blood compatibility and cell affinity. Interestingly, when the hydrophobic/hydrophilic balance of the (co)polymers was changed, macrophages could be activated without causing cytotoxicity. These unique (co)polymers have attractive characteristics that make them suitable replacements for PNIPAM, as well as promising functional materials with applications in many fields.